La tecnologia HERON per il Monitoraggio dello stato avanzamento lavori strutture verticali - Vassena, Giorgio (GEOmedia, 2021)
HERON mobile mapping system allows the introduction of SLAM technology inside construction sites of large buildings to monitor the work progress. The use of HERON at a vertical structure in Milan highlights the potential of the mobile mapping system produced by Gexcel. HERON allows performing rapid "as-built/as-designed" checks in this kind of structure when the accuracies involved are centimetric. Thanks to dedicated software, HERON can also use the "as-built" analysis for innovative solutions useful for construction site management, e.g. the digital site documentation, the geometric changes real-time verification, the construction phases progress monitoring, the site work progress document updating.